Chemical Ecology of the Parasitoid Wasp Genus Nasonia (Hymenoptera, Pteromalidae) - Mair, Magdalena M.; Ruther, Joachim (Frontiers in Ecology and Evolution, 2019)
The use of chemical cues and signals is essential for communication in insects. Wasps of the genus Nasonia (Hymenoptera, Pteromalidae) are gregarious parasitoids that lay their eggs into puparia of cyclorrhaphous flies. During their life cycle, various kinds of semiochemicals are used: (1) a male abdominal sex pheromone that attracts females and induces site fidelity in males, (2) a female-derived contact sex pheromone eliciting courtship behavior in males, (3) an oral male aphrodisiac eliciting receptivity signaling in females and causing a switch in the females’ olfactory preferences, (4) chemicals derived from host habitat and host puparia used in olfactory host finding by female wasps, and (5) chemicals used by females to assess the quality and parasitization status of potential hosts. We review the literature on the chemical ecology of Nasonia spp. following the wasps’ life cycle from emergence to oviposition. We depict biosynthetic pathways where available, discuss ecological implications, highlight differences among Nasonia species, summarize insights into their olfactory perception and associative learning abilities, and point out gaps in our understanding of the chemical ecology of these parasitoids to be addressed in future studies.